Analyzing Linguistic Complexity in Students' Presentations: A Multimodal Approach - Asbar Asbar; Hasan Hasan; Musdalifah Musdalifah; Ismail Ismail (Universitas Muhammadiyah Enrekang, 2024)
This study investigates linguistic complexity and multimodal strategies in student presentations, aiming to enhance understanding of effective communication in educational settings. The research employs a qualitative approach, analyzing verbal and non-verbal features from video recordings, interviews, and presentation materials of seventh-semester students. Results indicate a wide range of linguistic abilities, with vocabulary diversity and sentence complexity varying significantly among participants. Multimodal strategies, particularly the integration of verbal, visual, and gestural elements, were found to significantly enhance audience engagement. Challenges such as anxiety, language barriers, and technical difficulties were identified, with strategies like peer practice and feedback proving beneficial. The study highlights the importance of targeted support and technical training to improve presentation skills. These findings contribute to the existing knowledge by emphasizing the value of multimodal communication and suggesting practical approaches for educators. Future research could explore skill development over time and the impact of multimodal strategies in diverse educational contexts.